The dorsal raphe nucleus exerts opposed control on generalized anxiety and panic-related defensive responses in rats - Sena, L. M.; Bueno, C.; Pobbe, RLH; Andrade, TGCS; Zangrossi, H.; Viana, M. B. (Elsevier B.V., 2003)
It has been proposed that the ascending dorsal raphe (DR)-serotonergic (5-HT) pathway facilitates conditioned avoidance responses to potential or distal threat, while the DR-periventricular 5-HT pathway inhibits unconditioned flight reactions to proximal danger. Dysfunction on these pathways would be, respectively, related to generalized anxiety (GAD) and panic disorder (PD). To investigate this hypothesis, we microinjected into the rat DR the benzodiazepine inverse receptor agonist FG 7142, the 5-HT1A receptor agonist 8-OH-DPAT or the GABA(A) receptor agonist muscimol. Animals were evaluated in the elevated T-maze (ETM) and light/dark transition test. These models generate defensive responses that have been related to GAD and PD. Experiments were also conducted in the ETM 14 days after the selective lesion of DR serotonergic neurons by 5,7-dihydroxytriptamine (DHT). In all cases, rats were pre-exposed to one of the open arms of the ETM 1 day before testing. The results showed that FG 7142 facilitated inhibitory avoidance, an anxiogenic effect, while impairing one-way escape, an anxiolytic effect. 8-OH-DPAT, muscimol, and 5,7-DHT-induced lesions acted in the opposite direction, impairing inhibitory avoidance while facilitating one-way escape from the open arm. In the light/dark transition, 8-OH-DPAT and muscimol increased the time spent in the lighted compartment, an anxiolytic effect. The data supports the view that distinct DR-5-HT pathways regulate neural mechanisms underlying GAD and PD. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: dorsal raphe nucleus; serotonin; FG 7142; 8-OH-DPAT; muscimol; 5,7-dihydroxytriptamine lesions; generalized anxiety; panic